2020
DOI: 10.2147/idr.s253363
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Antibacterial Activity and Mechanism of Action of Luteolin Against <em>Trueperella pyogenes</em></p>

Abstract: Purpose: This research aimed to investigate the antibacterial activity and potential mechanism of luteolin against T. pyogenes. Materials and Methods: The broth microdilution method was used to determine the minimum inhibitory concentrations (MICs) of luteolin against various T. pyogenes strains. The potential mechanism of action of luteolin was elucidated through testing and analysing the luteolin-induced alterations of T. pyogenes in several aspects, including cell wall, cell membrane, protein expression, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 62 publications
1
42
0
Order By: Relevance
“…After being treated by SAEW for 15, 30, 45, and 60 s, the NPN fluorescence intensity of P. deceptionensis CM2 cells was increased by 202%, 255%, 266%, and 271%, respectively, compared to the untreated cells ( p < 0.05). These data indicate that SAEW disrupted the extracellular membranes of P. deceptionensis CM2 cells, which might contribute to the cell death [ 34 ]. Previous studies showed that AEW with high ORP caused the oxidation of sulfhydryl groups on cell surfaces and disturbed metabolic pathways inside the bacterial cells, which might be responsible for cell death [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…After being treated by SAEW for 15, 30, 45, and 60 s, the NPN fluorescence intensity of P. deceptionensis CM2 cells was increased by 202%, 255%, 266%, and 271%, respectively, compared to the untreated cells ( p < 0.05). These data indicate that SAEW disrupted the extracellular membranes of P. deceptionensis CM2 cells, which might contribute to the cell death [ 34 ]. Previous studies showed that AEW with high ORP caused the oxidation of sulfhydryl groups on cell surfaces and disturbed metabolic pathways inside the bacterial cells, which might be responsible for cell death [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement in the activity may be due to the higher solubility of LT in the presence of the used edge activator as well as the nano size of vesicles. Due to the higher solubility of LT, it showed activity by destroying the cell wall and cell membrane and inhibiting nucleic acid synthesis [54].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The main strategies by which luteolin affects bacterial proteins include binding to or interacting with proteins, decreasing the secretion of proteins, and inhibiting protein expression [29][30][31][32]. Our preliminary data suggest that luteolin can affect the expression of proteins and interfere with the normal processes of T. pyogenes [33]. Interestingly, luteolin also exerted a significant inhibitory effect on the production of the MATE protein in T. pyogenes by downregulating the expression of the MATE gene [34].…”
Section: Introductionmentioning
confidence: 75%
“…The T. pyogenes isolate BMH06-3 was collected from dairy cattle in Liaoning, China, and identified by 16S rRNA gene sequencing [33]. T. pyogenes strains were cultured on Mueller-Hinton agar (MHA, Solarbio, Beijing, China) containing 5% (v/v) sheep blood (Solarbio, Beijing, China) in an incubator (5% CO2) at 37 °C for 36 h, and the colonies were inoculated in nutrient broth (NB, Solarbio, Beijing, China) supplemented with 8% (v/v) fetal bovine serum (FBS, Gibco, Grand Island, USA).…”
Section: T Pyogenes Strains and Culturementioning
confidence: 99%
See 1 more Smart Citation